Strategi Komunikasi Bisnis Pada Produk MS Glow - Sepania Tiarasi Lumban Tobing; Linsa Febby Br Barus; Junedi Sugianto Pakpahan; Lenti Susanna Saragih; Danny Ajar Baskoro (Lembaga Pengembangan Kinerja Dosen, 2024)
To convey this, BMKG created an official Instagram account called @msglowbeauty so that the message is conveyed quickly and comprehensively throughout Indonesia. Of course, MS Glow has the right communication strategy on digital media so that the message can be conveyed well and is of course responded to by the public or at least read by the general public on Instagram social media. The aim of this research is to analyze the digital communication strategy on @msglowbeauty on Instagram. Here, of course, MS Glow uses social media in the form of Instagram as new media to convey various information about skin care. Of course, the thing that is taken into consideration is the high and increasing number of Instagram users from Indonesia every year so that Instagram is considered effective for conveying this information. Apart from that, the dominant market segment of Instagram users is millennials and adults. This is of course related to the communication strategy conveyed by Instagram @msglowbeauty because the information conveyed is quite scientific information and of course only understood by people who are growing up or adults.